Hybrid Learning Innovation: Challenges for Developing Teachers Skills in Indonesia - Maddukelleng Maddukelleng; Jihan Jihan; Heri Gunawan; Hary Murcahyanto; Waldimer Pasaribu (Sekolah Tinggi Ilmu Al-Qur'an (STIQ) Amuntai Kalimantan Selatan, 2023)
The world of education receives a fairly high impact due to developments in technology and information. In the 21st century there has been a shift from industrial technology to information technology, so that in the future this causes teachers as educators and essential elements in the field of education to be able to learn new things in the teaching and learning process, including learning innovations. This research will be conducted to see how the challenges and readiness of teachers as educators face the influx of technological changes and innovations in implementing learning. The approach used in this study is a descriptive qualitative approach with descriptive analysis methods. This research uses secondary data that comes from the results of research and previous studies. In selecting data, the researcher selects various studies and studies that are still relevant to this research. This study found that the rapid development of technology and information requires educators to keep abreast of technological developments by continuously improving themselves, innovating learning, and adapting to the needs of society. In facing the various challenges that exist in the future, educators need to have various skills in life and career, learning and innovation skills, as well as skills in using media and technology.